HOW DOES THE IN VIVO BILIARY ELIMINATION OF DRUGS CHANGE WITH AGE? EVIDENCE FROM CLINICAL DATA USING A SYSTEMS PHARMACOLOGY APPROACH. Issue 1 (14th December 2015) - Johnson, Trevor; Rowland-Yeo, Karen; Jamei, Masoud; Rostami-Hodjegan, Amin
Abstract : There is little information on the development of biliary drug elimination (BE) with age. The aims of this study were to collate literature data on the pharmacokinetics of biliary excreted drugs used in paediatrics and to apply a Physiologically Based Pharmacokinetic model to predict their systemic clearance (CLiv) across this age range. Drug parameters for azithromycin, ceftriaxone and digoxin were collated from the literature and validated against adult clinical data in Simcyp (V14R1). The change in CLiv with age was simulated in the paediatric model and compared to the observed data; the ontogeny function associated with BE was optimised in order to recover the age-related CLiv. For azithromycin (79% BE) a fraction of adult biliary excretion activity of 15% had to be assumed to be able to predict accurately the CL of the drug in neonates (24 to 28 weeks GA) whilst 100% activity was apparent by 7 months. For ceftriaxone (51% BE) full biliary excretion activity appeared to be present at full term birth. Finally, for digoxin (25% BE), a fraction of adult biliary excretion activity of 10% had to be assumed to predict the CL of the drug at birth whilst 100% activity was present by The ontogeny of BE for all three drugs appears to be rapid and reach adult levels at birth or in the first few months of postnatal age. More research is required in this area particularly on the ontogeny of specific canalicular transporters in humans.